Bioavailability Study of an Innovative Orobuccal Formulation of Glutathione. (16th November 2015) - Buonocore, Daniela; Grosini, Matteo; Giardina, Silvana; Michelotti, Angela; Carrabetta, Mariaelena; Seneci, Antonio; Verri, Manuela; Dossena, Maurizia; Marzatico, Fulvio
Abstract : Alteration of the ubiquitous thiol tripeptide glutathione (GSH) is involved in oxidative stress, which plays a role in ageing; consequently, GSH is closely related to this process characterized by progressive decline in the efficiency of physiological function and increased susceptibility to disease. When circulating GSH decreases, oral administration might be considered a therapeutic benefit. Unfortunately, due to the hydrolysis of the tripeptide by intestinalγ -glutamyltransferase, dietary glutathione is not a major determinant for its increase. Aim of this work was to evaluate improvement of GSH systemic availability testing, in vitro and in vivo, an optimized orobuccal fast-slow release formulation tablet containing pure stabilized GSH. In vitro evaluation of the penetration capability of the innovative GSH-release formulation showed that GSH was well absorbed by the reconstructed oral epithelium and its absorption has features of time-dependence. In addition, in vivo results, obtained from 15 healthy volunteers, were in favor of GSH level improvement in blood showing fast (after 30 and 60 minutes) absorption through oral mucosa. In conclusion, the intake of GSH formulated through optimized orobuccal fast-slow release tablets gave positive results in raising GSH blood concentration.